2022
DOI: 10.1002/advs.202204702
|View full text |Cite
|
Sign up to set email alerts
|

Blood‐Coagulation‐Inspired Dynamic Bridging Strategy for the Fabrication of Multiscale‐Assembled Hierarchical Porous Material

Abstract: Porous materials, from macroscopic bulk materials (MBs) with (sub‐)millimeter‐scale pores to tiny particles (TPs) with (sub‐)nanometer‐scale pores, have attracted ever‐growing interest in various fields. However, the integration of multi‐scale pores in one composite is promising but challenging, owing to the considerable gap in the scale of the pores. Inspired by blood coagulation, a fibrin‐based dynamic bridging strategy is developed to fabricate a multiscale‐assembled hierarchical porous material (MHPM), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Scanning electron microscopy (SEM, Figure d) further revealed that there were fewer and larger pores in the thick BSP layer, in remarkable contrast to the denser and smaller micropores in the thin PNS@CMCS layer. The cross-linking degree of hydrogels and solid contents have been recognized as critical factors to affect the microstructure and pore sizes of lyophilized hydrogel sponges. , In our study, the BSP-containing carbomer sponges with less carbomer content even showed more loose porous structures (Figure S2), indicating the loose cross-linking and low solid contents in the BSP layer. By contrast, the lyophilized PNS-containing CMCS hydrogels with the higher alginate contents showed denser structures (Figure S3), suggesting a large cross-linking degree and high solid contents in the BSP layer.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Scanning electron microscopy (SEM, Figure d) further revealed that there were fewer and larger pores in the thick BSP layer, in remarkable contrast to the denser and smaller micropores in the thin PNS@CMCS layer. The cross-linking degree of hydrogels and solid contents have been recognized as critical factors to affect the microstructure and pore sizes of lyophilized hydrogel sponges. , In our study, the BSP-containing carbomer sponges with less carbomer content even showed more loose porous structures (Figure S2), indicating the loose cross-linking and low solid contents in the BSP layer. By contrast, the lyophilized PNS-containing CMCS hydrogels with the higher alginate contents showed denser structures (Figure S3), suggesting a large cross-linking degree and high solid contents in the BSP layer.…”
mentioning
confidence: 59%
“…30−32 Although these elements have been used in different dressings, in terms of the management of hemorrhagic wounds, 33,34 current dressings are still lacking to meet the demands of coordinated hemostasis and angiogenesis during the whole stages of wound healing. 35,36 In this paper, our design of the double-layer BSP-PNS@ CMCS dressings along with the stepwise treatment strategy is expected for the advanced management of hemorrhagic wounds. The desired dressing (BSP-PNS@CMCS) with natural skin-mimicking asymmetric double-layer structures was fabricated via a two-step approach of lyophilizing BSP and PNS-laden CMCS hydrogels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The nano/micro‐structure of materials can be manipulated to increase catalytic efficacy by enlarging contact areas. [ 220,237 ]…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%